Modified Mocaf Flour (Modified Cassava Flour) as Alternative Culture Media for Growth Bacteria Escherichia coli and Bacillus cereus: Modifikasi Tepung Mocaf (Modified Cassava Flour) Sebagai Media Kultur Alternatif Untuk Pertumbuhan Bakteri Escherichiacoli dan Bacillus cereus - Rini, Chylen Setiyo; Saidi, Ida Agustini; Rohmah, Jamilatur (Universitas Muhammadiyah Sidoarjo, 2022)
Media is a means of growth of microorganism that contain nutrients needed by microorganisms. The high price of media and teh use of natural resources used as growth media has not been maximized, spurring researchers to find alternative media from local materials such as mocaf flour (modified cassava flour) which is a derivative product of cassava with processing techniques using the principle of fermentation by lactic acid bacteria. The purpose of thus study was to determine the number of colonies of Escherichia coli and Bacillus cereus bacteria that grew on laternative media of mocaf flour. This research is an experimental laboratory with variations in the mass of mocaf flour 1 grams, 2 grams, 4 grams, 6 grmas, 8 grams, positive controls and negative controls, the data obtained were analyzed using ANOVA test. The results showed that the average number of positive control colonies from Escherichia coli was 22.5 x 105 CFU/mL, while the positive control colonies from Bacillus subtilis were 20.25 x 105 CFU/mL. The highest average vakue of variations in the concentration of alternative media using mocaf flour (modified cassava flour) as much as 8 grams on Escherichia coli is 81 x 105 CFU/mL while Bacillus subtilis is 197.75 x 105 CFU/mL using mocaf flour (modified cassava flour) as much as 8 grams. The average value of the lowest colony number of Escherichia coli bacteria in 1 grams mocaf flour mass in 7.25 x 105 CFU/mL, for Bacillus subtilis the lowest average colony value in 2 grams mocaf flour is 27 x 105 CFU/mL. Each of treatment has a significant value of 0.05 meaning that there is no significant difference between NA medium and mocaf flour alternative media